(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The closed contour of a band-saw blade is a bright example to the theme of the internally statically indeterminate schemes in the Strength of Materials syllabus of the students in Wood Technology at Sofia University of Forestry. An original model is proposed aimed at strength and deformation calculations of the blade which embraces the two wheels of the band-saw. The internally statically indeterminate structure problem is solved in a way in which the stu-dents are taught. At an instant position of the blade, the tensile stress is determined at various blade‟s points taking into account the assembly pre-tension, the cutting force, the bending of the blade at the wheel periphery, and the heating. The stress at any point, while traveling onto the blade contour, varies and follows an oscillogram with complicated, random variations. Under such conditions, the blade is threatened by metal fatigue. A basic, approximate oscillo-gram has been theoretically obtained which will be complicated with additional waves in next studies. Application of the Integration of Damage Differentials (IDD) method is envisaged for fatigue life assessment as developed in the Faculty of Forest Industry. As well, the study done is envisaged to continue into possible diploma and doctoral theses of the students instructed also by professors in next school subjects. Then, additional dynamic phenomena can be in-volved in the calculation model, and loading spectra under different regimes of cutting can be built, etc.